2019
DOI: 10.3390/biom9120753
|View full text |Cite
|
Sign up to set email alerts
|

Genomic, Transcriptomic and Enzymatic Insight into Lignocellulolytic System of a Plant Pathogen Dickeya sp. WS52 to Digest Sweet Pepper and Tomato Stalk

Abstract: Dickeya sp., a plant pathogen, causing soft rot with strong pectin degradation capacity was taken for the comprehensive analysis of its corresponding biomass degradative system, which has not been analyzed yet. Whole genome sequence analysis of the isolated soft-rotten plant pathogen Dickeya sp. WS52, revealed various coding genes which involved in vegetable stalk degradation-related properties. A total of 122 genes were found to be encoded for putative carbohydrate-active enzymes (CAZy) in Dickeya sp. WS52. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…CAZy annotation showed that there are more genes in A. japonicas PJ01 related to carbohydrate activity than Dickeya sp. WS52, which can also produce pectinase, cellulase and xylanase [38]. Xylanase can be used as an auxiliary enzyme to improve the hydrolysis efficiency of cellulase [39].…”
Section: Discussionmentioning
confidence: 99%
“…CAZy annotation showed that there are more genes in A. japonicas PJ01 related to carbohydrate activity than Dickeya sp. WS52, which can also produce pectinase, cellulase and xylanase [38]. Xylanase can be used as an auxiliary enzyme to improve the hydrolysis efficiency of cellulase [39].…”
Section: Discussionmentioning
confidence: 99%
“…When the germinating spores were separated from the chitosans, the spore germination and infection against F. concentricum were recovered, whereas no water‐soaked lesions and soft rot were observed at the infection sites. Generally, soft rot is due to the secretion of a battery of pectinases which acts by destroying the integrity of the plant cell wall (Yang, Lin et al, 2019). In this study, 0.5 g/L of HMC or WSC may inactivate the pectinase activity, which to some extent damaged the infection capacity of F .…”
Section: Discussionmentioning
confidence: 99%
“…Digging up the genomic, transcriptomic and enzymatic information of a pectin-degrading, lignocellulolytic and plant pathogenic bacteria Dickeya sp. WS52 revealed 122 genes encoding putative carbohydrate-active enzymes (CAZy) and also a higher number of pectin degrading genes [35]. The study further revealed significant up-regulation of the genes encoding lignocellulolytic enzymes in the bacterium in minimal salt medium with vegetable stalks, and the findings constitute a lignocellulolytic system having immense importance in bioenergy industry and animal production.…”
mentioning
confidence: 82%